[Staff training at Caroni (1975) Limited] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
A training session for the Caroni (1975) Ltd.'s tradesmen at the Training Centre at Sevilla House.
Cataloger's title
Keywords: Sugar industry -- Employees-Training of -- Trinidad and Tobago